Acquisition of a Leucine Zipper Motif as a Mechanism of Antimorphy for an Allele of the Drosophila Hox Gene Sex Combs Reduced. Issue 5 (1st May 2014) - Sivanantharajah, Lovesha; Percival-Smith, Anthony
Abstract: In 1932, Müller first used the term "antimorphic" to describe mutant alleles that have an effect that is antagonistic to that of the wild-type allele from which they were derived. In a previous characterization of mutant alleles of the Drosophila melanogaster Hox gene, Sex combs reduced ( Scr ), we identified the missense, antimorphic allele Scr 14, which is a Ser10 -to-Leu change in the N-terminally located, bilateran-specific octapeptide motif. Here we propose that the cause of Scr 14 antimorphy is the acquisition of a leucine zipper oligomerization motif spanning the octapeptide motif and adjacently located protostome-specific LASCY motif. Analysis of the primary and predicted secondary structures of the SCR N-terminus suggests that while the SCR + encodes a short, α-helical region containing one putative heptad repeat, the same region in SCR 14 encodes a longer, α-helical region containing two putative heptad repeats. In addition, in vitro cross-linking assays demonstrated strong oligomerization of SCR 14 but not SCR + . For in vivo sex comb formation, we observed reciprocal inhibition of endogenous SCR + and SCR 14 activity by ectopic expression of truncated SCR 14 and SCR + peptides, respectively. The acquisition of an oligomerization domain in SCR 14 presents a novel mechanism of antimorphy relative to the dominant negative mechanism, which maintains oligomerization between the wild-type and mutant protein subunits.